Assessing education as a determinant of trust in South Africa - Sigauke, Simphiwe Ntombizodwa (School of Economics, 2025)
It has been argued that one of the key benefits of raising the levels of education in a nation is the enhancement of trust. Trust has been found to be a critical driver of economic development and growth and is thus of particular value to South Africa. There has been rising literature, however, showing the ineffectiveness of education as a policy tool to increase trust levels. At times the impact of education has even been found to impair trust within a society. This present study sought to expand the research interrogating education as a determinant of interpersonal trust in South Africa by assessing the impact of education on various forms of trust. In this thesis, education as a determinant of trust in South Africa was assessed using the National Income Dynamics Wave 5 Cross-Sectional data set. As a primary focus, an analysis was undertaken to assess the relationship between education and trust by applying probit regression analysis in which the years of basic education obtained together with control variables was regressed against five variables of trust. In a secondary analysis, the household spillover effects of education on trust were also assessed. The results of the study suggest that an additional year of basic education increases the likelihood of trusting in respect of only two forms of trust: trust of people that an individual knows and trust of one's own race group. Basic education was found to be an insignificant determinant of the other three forms of trust. The result for trust of one's own race group was further confirmed in the spillovers analysis. Here, the results suggested that education household spillovers that impact trust are present between the household head and the other members of the household. The spillover effects of education here were found to enhance in-group trust in terms of one's own race group on the one hand and to reduce out-group trust in terms of other race groups on the other hand. Notably, however, the impact of basic education on trust observed in both the primary and secondary analysis was quite minimal. Evidence from this study therefore supports the sentiment expressed in the literature that the positive outcomes of education on trust are most certainly not universal. Rather, the nature of this relationship is variable as a consequence of a number of contextual dynamics within the society in question.